The role of hamza agha in the uprising of sheikh obaidullah al-nahri 1880-1881 - Taha Jameel , Zina; Hassa Youssef, Fakher (Humanities Journal of University of Zakho, 2023)
The precent research investigates the role of Hamza Agha , the leader of Mangur, in the uprising of Shekh Obaidullah Nahri (1880-1881). Hamza Agah joined the uprising because of the policy adopted by the Iranian government in the Kudish regions. The Iranian government imposed high taxes on the Kurdish tribes and Aghas, among them was Hamza Agah and his tribe. As a result, he stood against this policy. As a matter of fact, the same policy was adopted aginst Hamza Agah and the same reason made the Iranain government arrest him for a long time. As a result, Hamza Agha had no choice but to join the Uprising of Shekh Obaidullahi Nahri to avoid reapeating such events and also to be a part of the first national Kurd uprising to get their national rigths. Hamza Agha was aware of his attempts and meetings to start uprising aginst both Ottoman and Qajar governments. He sent someone to inform Shekh Obaidullah about the situation. At the end, Shekh Obaidulah helped him, and made him the commander in chief leading that front with his son Sheikh Abdulqadir, the reason behind that was his familiarty of the area. Actually, following the plans they were able to control the Kurdish areas. They continued in their progress in such areas and they were about to reach Tabriz. Because of the great military support sent by Shah and the betrayal of some Kurdish leaders participated in the fight, he was obliged to withdraw from such areas with many people particpated in the fight against the Iranians toward the borders of Ottoman.